The impacts of scallop dredging on sponge assemblages in the Gulf of kalloni (Aegean Sea, northeastern Mediterranean). - Kefalas, E.; Castritsi-Catharios, I; Miliou, H. (ICES Journal of Marine Science, 2003)
Concerns have been raised on the impact of bottom-fishing activities in the shallow Gulf of Kalloni (Lesvos Island, Aegean Sea). Fishing with demersal gears was banned in 1995, but the Gulf was reopened in 1998 only for scallop dredging using the ‘‘lagamna’’ gear. Two series of samplings were done with this gear in 1998 and 1999 (October) before the beginning of scallop-fishing period (from November up to March), aiming to investigate possible changes in sponge assemblages. Sponges (Porifera) were the most abundant mesomegafaunal benthic organisms in the Gulf, besides scallops and other bivalves. Total abundance, number of species, species diversity, species richness and evenness of sponge assemblages reduced significantly from the year 1998 to 1999. The population of the excavating Cliona celata, the only infaunal sponge species found in the Gulf, decreased. Multivariate analysis on the abundance data of epibenthic sponge species revealed a clear separation of samples collected during the 2 years, indicating changes in the structure of sponge assemblages. The distinguishing species included a variety of growth forms: massive (Mycale massa, Suberites domuncula and Tethya citrina), lobose (Suberites massa, Tedania anhelans and Halichondria panicea), erect branching (Raspailia viminalis), encrusting (Crambe crambe) and cushion-shaped (Mycale contarenii and Chondrilla nuculla) sponges. Among these species, only S. massa increased its abundance in 1999. All others decreased. No significant loss of information occurred when multivariate analysis was applied to abundance data of genera or families. This comparative study demonstrated that the time interval between two consecutive scallop-fishing periods was insufficient for the recovery of sponge assemblages. It is concluded that scallop dredging causes long-term changes in the structure and biodiversity of sponge assemblages in the Gulf of Kalloni. An improved strategy of fishery management is required in future for the conservation of living resources in this Gulf.